Verbaal geweld in de Nederlandse literaire kritiek: Het Brusselse tijdschrift De Argus 1825-1826 - Weijermars, Janneke (Department of Dutch and South African Studies, Faculty of English, 2011)
During the United Kingdom of the Netherlands 1815-1830, when the Low Countries were united under king Willem I, a new Dutch literary review De Argus was published in Brussels. The editors had the intention to build up a Dutch literature for the whole new nation, with originality, patriotism and simplicity as its features, but they used unorthodox methods to achieve their goals. In this study we investigate the traditional and new aspects of De Argus’s reviews. For that we will zoom in on the principle of politeness, which was normally used by late eighteen-century and early nineteen-century reviewers to protect an open literary debate.
Verbal Abuse in the Dutch Literary Reviewing: The Brussels Review De Argus 1825-1826
Keywords: United Kingdom of the Netherlands; literary review; Lodewijk Gerard Visscher; nineteenth century; Jan Wap